Formulation and Evaluation of the Physical Properties of Clay Mask Containing Ethanol Extract of Kenikir (Cosmos caudatus) Leaves - Puspawan Hariadi; Rina Sri Apriani; Baiq Maylinda Gemantari; Tri Puspita Yuliana; Erma Ewisa Oktresia; Fitriwati Sovia (Journal of Pharmacology Experiment and Pharmaceutical Technology, 2025)
The demand for natural-based cosmetic products continues to increase due to their perceived safety and minimal side effects. Kenikir leaves (Cosmos caudatus Kunth) are known to contain active compounds such as flavonoids, tannins, and phenols, which have antioxidant potential and can be utilized in facial mask preparations. This study aims to formulate a clay mask preparation from the ethanol extract of kenikir leaves and evaluate its physical properties. The extract was obtained through maceration using 96% ethanol, and then formulated into three concentrations: F1 (0.5%), F2 (1%), and F3 (2%). The evaluation of the preparation included organoleptic tests, adhesion test, spreadability test, and pH measurement. The results showed that F1 had a pH of 6, adhesion time of 2 seconds, and spreadability of 5.3 cm. F2 had a pH of 6, adhesion time of 2 seconds, and spreadability of 5.2 cm. F3 had a pH of 6, adhesion time of 4.6 seconds, and spreadability of 5 cm. The evaluation results indicated that all clay mask formulations met the physical quality criteria for clay masks.